DENTAL PROFESSION STUDENTS’ PERCEPTIONS OF HEPATITIS B PREVENTION AND TRANSMISSION BASED ON THE HEALTH BELIEF MODEL - Angeline Sofia Natasha; Marta Juslily; Goalbertus Goalbertus (FKG ULM, 2025)
Background: Dental professional students are at high risk of being infected with the Hepatitis B virus due to their exposure to saliva, blood and droplets during most dental procedures. Various preventive measures have been taken, including education and implementation of infection control precautions. Therefore, the perceptions of dental professional students can influence their behavior in preventing transmission of the Hepatitis B virus. The Health Belief Model was used to determine the perceptions of dental professional students regarding the prevention and transmission of the Hepatitis B virus. Purposes: To determine the perceptions of dental professional students regarding prevention and transmission of the Hepatitis B virus based on the Health Belief Model. Methods: This study employed a qualitative descriptive approach with in-depth interviews. Information was collected from 10 informants and 1 key informant through in-depth interviews. Results: 8 of 10 informants perceived high susceptibility to Hepatitis B due to patient contact. Prevention of the Hepatitis B virus provided benefits to the informants even though there were several obstacles to its implementation, such as unfavorable environmental factors and financial limitations. Despite environmental and financial barriers, strong self-efficacy and institutional cues supported preventive behaviors. These findings suggest that reinforcing institutional support and addressing external barriers may enhance preventive behaviors among dental professional students. Conclusion: Based on their perceptions, it is very possible for informants to maintain preventive behavior against the Hepatitis B virus inside and outside the hospital area. Keywords: Dental Professional Students, Health Belief Model, Hepatitis B, Perception, Prevention.